Experimental research of stability of rectilineal motion of tractor in the conditions of a different coupling of driving-wheels - Лихвенко, С. П.; Харак, Р. М. (Scientific Progress & Innovations, 2012)
In the article results of experimental research of stability of rectilinear motion of the MTZ-80 tractor are represented during work on a surface with a different coupling of wheels and quiescent load on a hook depending on the rate of movement. It is set that for providing of rectilinear motion at the differential drive of wheels of back bridge it is necessary to turn the front wheels of tractor on the average on a corner 2,18 degrees, and at the hardly blocked drive - on 5,16 degrees. It is multiplied the corner of turn of wheels at growth of rate of movement of tractor. Measurement of parameters were carried out with the use of tensometric devices.